2019
DOI: 10.1155/2019/4652596
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 Gene-Modified Bone Marrow-Derived Dendritic Cells Attenuate Liver Fibrosis in Mice by Inducing Regulatory T Cells and Inhibiting the TGF-β/Smad Signaling Pathway

Abstract: Aim To explore the therapeutic effects and mechanisms of interleukin 10 gene-modified bone marrow-derived dendritic cells (DC-IL10) on liver fibrosis. Methods In vitro, BMDCs were transfected with lentiviral-interleukin 10-GFP (LV-IL10-GFP) at the MOI of 1 : 40. Then, the phenotype (MHCII, CD80, and CD86) and allo-stimulatory ability of DC-IL10 were identified by flow cytometry, and the levels of IL-10 and IL-12 (p70) secreted into the culture supernatants were quantified by ELISA. In vivo, DC-IL10 was injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
4
24
0
2
Order By: Relevance
“…However, despite the more mature phenotype, the DCs transfected with pIL-10 as well as with pMHC induced FoxP3 + Tregs and IL-10 + CD4 + cells in cocultures with autologous splenocytes at similar levels to immature nonelectroporated DCs ( Figure 3 ). These findings correspond to the researches showing that immature DCs [ 17 , 18 ], IL-10-producing DCs [ 5 , 6 , 21 23 ], and antigen-loaded DCs [ 8 , 17 , 18 ] are able to induce CD4 + IL-10 + cells and FoxP3 + Tregs. In our opinion, the level of suppression which corresponds to that of nonelectroporated immature DCs is enough and expected, as the effect of this group, in fact, more closely reflects that of the immature DCs taking part in immunoregulatory processes in vivo than other groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, despite the more mature phenotype, the DCs transfected with pIL-10 as well as with pMHC induced FoxP3 + Tregs and IL-10 + CD4 + cells in cocultures with autologous splenocytes at similar levels to immature nonelectroporated DCs ( Figure 3 ). These findings correspond to the researches showing that immature DCs [ 17 , 18 ], IL-10-producing DCs [ 5 , 6 , 21 23 ], and antigen-loaded DCs [ 8 , 17 , 18 ] are able to induce CD4 + IL-10 + cells and FoxP3 + Tregs. In our opinion, the level of suppression which corresponds to that of nonelectroporated immature DCs is enough and expected, as the effect of this group, in fact, more closely reflects that of the immature DCs taking part in immunoregulatory processes in vivo than other groups.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, increased FoxP3 + Treg frequencies were observed only in the DCpMHC and the DCpIL-10 + pMHC groups 3 weeks post-GVHD induction despite the fact that DCs transfected with IL-10 were capable of Treg induction in MLCs. According to the previous findings, in vivo Treg generation by IL-10-producing DCs requires allogeneic [ 21 ] or antigen-loaded [ 27 ] DCs. By contrast, Tregs can be generated in vitro with syngeneic non-antigen-loaded IL-10 producing DCs [ 22 ].…”
Section: Discussionmentioning
confidence: 98%
“…We found that TGF-β1-stimulated activation of ERK1/2 and p38 was also dose-dependently inhibited by melatonin, whereas JNK1/2 phosphorylation was not affected. Previous studies have shown that Smad and MAPK signaling pathways play an important role in EMT stimulated by TGF-β1 [31][32][33] and the development of liver fibrosis [34][35][36][37]. Taken together, these results suggest that melatonin prevents EMT stimulated by TGF-β1 in AML12 hepatocytes through suppression of Smad and MAPK signaling cascades.…”
Section: Discussionsupporting
confidence: 57%
“…For example, promoting the expression of IL-10-related genes in DC could attenuate liver fibrosis in mice via increasing Treg induction. This kind of IL-10 + DC is characterized by low expression of costimulatory molecules ( 69 ). Nuclear paraspeckle assembly transcript 1 (NEAT1) is proven to use NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasomes as molecular decoys for miR-3076-3p, so knockdown NEAT1 could facilitate the tolerogenic phenotype in DC, which prevents progression of experimental autoimmune myocarditis and induces immune tolerance in a heart transplantation model ( 70 ).…”
Section: The Ex Vivo Induction Of Tol-dcmentioning
confidence: 99%